(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Purpose: The purpose of this study is to identify differences in the sociodemographic characteristics between the elderly who received help (hereinafter referred to as met “needs for help” or “met needs”) and those who did not (hereinafter referred to as “unmet needs for help” or “unmet needs”) among the elderly in need of help due to cognitive decline, and identify the sociodemographic factors that affect the unmet needs for help. Study method: This study is a secondary data analysis study using raw data from the Community Health Survey 2020 conducted in 2019 [15], and 21,880 elderly persons who answered that they needed help due to cognitive decline were selected from among the elderly population aged at least 65 years, and their answers were analyzed. For data analysis, the chi-square test and the Mann-Whitney U test were conducted using SPSS 23.0 to compare whether help was needed and whether the need was met, and logistic regression analysis was conducted to identify factors that affect unmet needs. Study results: Among the sociodemographic characteristics, gender, age, whether the person lives alone, whether the person has a spouse, income levels, and whether the person conducts economic activities showed significant differences depending on whether the respondent’s need for help was met. As for factors influencing unmet need for help, age, whether the person lives alone, and income level were shown to have significant effects, and whether the respondent has a spouse, whether the respondent conducts economic activities, and education level were shown to have no significant effects. Conclusions: Women, those who live alone, those who have no spouse, groups with low economic levels, and groups with low education levels were identified as vulnerable groups with a high level of need for help and high level of unmet needs that were not sufficiently helped. In addition, it was identified that the ratio of unmet needs was higher among those who were younger, who lived alone, and those with lower income levels. Therefore, attention to these groups in health programs is necessary to prevent cognitive decline in elderly persons.